Literasi Informasi dalam Menghadapi Berita Palsu: Analisis Bibliometrik Penyebaran di Media Sosial - Kurniawan, Wawan (Media Pustakawan, 2024)
The study's objective is to map the distribution of key publications on this topic, identify leading journals in this domain, analyze the most cited sources, examine trends based on keyword and treemap analyses, and explore keyword network maps and country-based network maps. The bibliometric analysis utilized data extracted from Scopus, employing the search syntax TITLE-ABS-KEY ( “information literacy” AND (“fake news” OR “misinformation” OR “disinformation”) AND (“social media”) ) AND ( LIMIT-TO ( DOCTYPE , “ar” ) OR LIMIT-TO ( DOCTYPE , “cp” ) ) AND ( LIMIT-TO ( LANGUAGE , “English” ) ). The collected documents were analyzed using R-biblioshiny. From the period of 2015 to 2023, we identified 103 documents focusing on information literacy's role in identifying and countering fake news on social media. These documents were published across 79 distinct sources, with an average citation rate of 24.33 per document. Predominant keywords within the research field include information literacy, fake news, social media, digital literacy, misinformation, media education, and critical thinking. This study highlights the evolving dialogue on information literacy and its crucial role in navigating the challenges posed by fake news on social media, offering insights into future research directions and policy development.